Do Transitions from Liberation Movements to Political Parties Guarantee Good Governance? The Case of ZANU-PF and the ANC (The Strategic Review for Southern Africa, 2021)
The purpose of this study is to examine the transition of liberation movements into political parties and whether that guarantees good governance or not. Since the end of the Second World War and the Cold War, the number of democratic states has increased on all continents. African states began to explore democratic governance from independence and the end of apartheid. Furthermore, the liberation struggle fought by many African movements led to independence and ‘decolonisation’. The emergence of these liberation movements was to emancipate and liberate their respective states so that the rule of oppressive imperialists such as the British could come to an end. The transition of the former colonial states ensured that the movements which fought the liberation struggle turned into political parties. The study uses the cases of the Zimbabwe African National-Patriotic Front (ZANU-PF) in Zimbabwe and the African National Congress (ANC) in South Africa to interrogate the transition into political parties and examine if good governance has been achieved because of that. The study has found that the implications of former liberation movements turning into political parties have not had the foreseen intentions. With the neopatrimonial theory, the study substantially examines whether ZANU-PF and the ANC have been in accordance with or against the dynamics of good governance informed by liberalism values.